STRESS AMONG INTERNATIONAL MEDICAL STUDENTS DURING COVID-19 PANDEMIC: A CROSS-SECTIONAL STUDY: STRESS AMONG STUDENTS DURING COVID-19 PANDEMIC - Milanovic, Maja; Mijatovic, Emilia; Djokic, Milena; Stanisavljevic, Tamara; Djokic, Ana; Milic, Nikola; Cirkovic, Andja; Rajović, Nina (Medicinski podmladak, 2022)
ABSTRACT INTRODUCTION: The aim of this study was to investigate the prevalence of stress among international medical students and factors associated with higher level of student’s stress during COVID-19 epidemic in Serbia. MATERIAL AND METHODS: The cross-sectional study was conducted using a five-section online questionnaire during January, 2021 among international medical students attending the Faculty of Medicine University of Belgrade, Studies in English in Serbia, using snowball sampling method. RESULTS: A total of 52 international medical students with mean age of 21.0±2.2 years, 58% female, were enrolled. Stress level was rated higher than usual in 65% of students. The predictors of higher level of stress were: being not prepared for full online courses (p=0.058), worry about own health (p=0.04), worry about health of loved ones (p=0.058), concern about financies (p=0.004) and exams/future study plans (p=0.033), lack of energy (p=0.012), strong emotions or mood swings (p=0.004) and inability to get things needed from stores (p=0.054). Fear or worry about health of their loved ones, concern about money as well as concern about exams or future study plans were independent predictors of the respondents’ higher level of stress in multivariate analysis. CONCLUSION: The COVID-19 pandemic has led to an increase in the level of stress among the international medical students in Serbia. Higher level of stress was associated with fear about health of loved ones, concern about finances and exams/future study plans.